Окна: [роман] / Дина Рубина ; живопись Бориса Карафелова - Рубина Дина Ильинична (Большая литература, 2012)
Экземпляры: Ф. 2 (20210330) / Инвентарный номер: 43414 / Цена: 192.15 / Сис.шифр: 84(2Роc=Рус)6 / Авт.знак: Р 82 / ГРНТИ: 17.82 / ББК: 84(2Роc=Рус)6